Virtual Property Pada Game Online Dalam Perspektif Hukum Ekonomi Syariah - Misno Misno (Al Maal: Journal of Islamic Economics and Banking, 2021)
The development of technology has brought a variety of high-tech entertainment, one of which is developing games (games) both offline and online. Online games are games that are widely enjoyed, especially by children and teenagers. Today's online game play is not just a game, but in it there are economic activities in the form of buying and selling which have an effect on ownership of virtual objects (Virtual Property. The conclusion of this study is that Virtual Property can be recognized as a treasure in Islam. Although it does not have a real form, there is a value that is recognized by the community so that it becomes part of the property. Because it is recognized as property, buying and selling with this object is permissible and lawful. Recognition of the existence of virtual property is based on the theory of urf, namely that everything that is considered good and permissible by the community can then be a legal argument.